Medical management and antiepileptic drugs in hypothalamic hamartoma. (7th June 2017) - Helen Cross, J.; Spoudeas, Helen
Summary: Hypothalamic hamartoma may present with epilepsy, specifically gelastic or dacrystic seizures, or endocrine dysfunction, commonly precocious puberty. The epilepsy in many patients is drug resistant, and has a high association with progressive cognitive, learning and behavioral difficulty. Medical treatment of seizures remains problematic, with many resistant to drug treatment. Surgical resection, or disconnection of the hamartoma provides the optimal chance of seizure control but with a relatively high risk of endocrine dysfunction, the result of interference with the hypothalamic‐pituitary axis in many. Careful assessment and monitoring by specialist centers with discussion of optimal intervention is required for individual cases.